Formulation of Essential Oils as Mosquito Repellent - Dwi Setyaningsih; Fitriana Roselly; Neli Muna (Journal of Tropical Pharmacy and Chemistry, 2020)
Essential oil has complex chemical substances with a lot of benefit, one of them is as mosquitoe or insect repellent. This research aims to find out the best essential oil formula for mosquito repellent. Essential oils that used in this research are citronella, lemongrass, cajeput, and lavender oil. Essential oils are characterized by its color, density, refractive index, and solubility in alcohol. The essential oil colors met the SNI which was pale yellow to clear yellow, the density was 0.8125 - 0.9114 g/ml, the refractive index was 1.4568-1.4665 and soluble in alcohol. The essential oil mixture resulted in 7 series of formula, namely series A1-A5, B1-B5, C1-C5, D1-D5, E1-E5, F1-F5, and G1-G5. The organoleptic test performed on all formula showed that the preferred formula was the formula E3, G3, and F3. All preferred formula were carried out repellent tests against mosquitoes to determine the effectiveness of the oil mixture in Virgin Coconut Oil (VCO) carrier. The result showed that E3 was more effective repellent compare to F3 and G3 formulas, because it has protection value more than 90% until fourth-hour.